Calidad educativa: ¿cómo formar un abogado de calidad y no morir en el intento? - Torres Morales de Ferreyros, Sylvia Amelía (2010)
This article outlines the three main factors that, according to the author 's opinion, are crucial for a higher education institution to train high quality professionals in a society where the individual interest often prevails over the collective interest. The career in law is taken as an example - a career that is pursued by thousands of youngsters: future lawyers. The question is, Did all of them received a high quality education that enables them to face the great challenges that we have in our society?